2021
DOI: 10.3390/jcs5100259
|View full text |Cite
|
Sign up to set email alerts
|

Toughening of Bioceramic Composites for Bone Regeneration

Abstract: Bioceramics are widely considered as elective materials for the regeneration of bone tissue, due to their compositional mimicry with bone inorganic components. However, they are intrinsically brittle, which limits their capability to sustain multiple biomechanical loads, especially in the case of load-bearing bone districts. In the last decades, intense research has been dedicated to combining processes to enhance both the strength and toughness of bioceramics, leading to bioceramic composite scaffolds. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 275 publications
(289 reference statements)
0
8
0
Order By: Relevance
“…In most cases, it is necessary to increase the bending strength, reduce elasticity, and avoid material failure. As a positive effect, it was reported that the fracture toughness and flexural strength of bioceramics increased in wet environments [ 85 ]. To overcome the above limitation, the usage of bioceramic coatings and the development of nanocomposite ceramics should be considered as appropriate approaches [ 86 , 87 ].…”
Section: Ceramic Materials For Biomedical Applicationsmentioning
confidence: 99%
“…In most cases, it is necessary to increase the bending strength, reduce elasticity, and avoid material failure. As a positive effect, it was reported that the fracture toughness and flexural strength of bioceramics increased in wet environments [ 85 ]. To overcome the above limitation, the usage of bioceramic coatings and the development of nanocomposite ceramics should be considered as appropriate approaches [ 86 , 87 ].…”
Section: Ceramic Materials For Biomedical Applicationsmentioning
confidence: 99%
“…Bioceramic is an important biocompatible ceramic material with excellent bioactivity, chemical stability, thermal resistance, and tissue-like mechanical characteristics. Bioceramics have been used as a nanoporous scaffold material to repair and reconstruct damaged tissues, fill bone defects, and deliver drug molecules [ 139 , 140 , 141 , 142 ]. Bioceramics, such as calcium phosphate and hydroxyapatite, can be extracted from natural waste materials (eggshell, bovine bone, fish bone, and seashells), which are widely geographically available at low cost.…”
Section: Sustainable Nanomaterials For Biomedical Applicationsmentioning
confidence: 99%
“…The crucial factors for scaffold materials are their toughness and porosity [215]. It is also important to study and determine how the daily activities of humans affect the fatigue life of porous scaffold implants [216].…”
Section: Future Perspectives and Possible Limitationsmentioning
confidence: 99%